2005
DOI: 10.5694/j.1326-5377.2005.tb06700.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage at diagnosis and cancer survival for Indigenous Australians in the Northern Territory

Abstract: Objective: To investigate whether Indigenous Australians with cancer have more advanced disease at diagnosis than other Australians, and whether late diagnosis explains lower Indigenous cancer survival rates. Design: Retrospective cohort study. Setting and participants: Indigenous and non‐Indigenous people diagnosed with cancers of the colon and rectum, lung, breast or cervix and non‐Hodgkin lymphoma in the Northern Territory of Australia in 1991–2000. Main outcome measures: SEER summary stage of cancer at dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 4 publications
9
80
4
1
Order By: Relevance
“…Although the numbers in our cohort were small and so the results lacked statistical precision, we identified disparities in cancer treatment delivery which should be further investigated and addressed by health service personnel. Although survival from head and neck cancer in Indigenous populations has not been reported elsewhere, the results of this study are consistent with the poor cancer survival and worse mortality that has been extensively reported for Indigenous people in Australian with other cancers [24,25]. We were unable to adjust for the presence of HPV which has been found to be a predictor of survival in whites in America [26] as HPV testing was not routinely undertaken at the time of the study.…”
Section: Discussionsupporting
confidence: 91%
“…Although the numbers in our cohort were small and so the results lacked statistical precision, we identified disparities in cancer treatment delivery which should be further investigated and addressed by health service personnel. Although survival from head and neck cancer in Indigenous populations has not been reported elsewhere, the results of this study are consistent with the poor cancer survival and worse mortality that has been extensively reported for Indigenous people in Australian with other cancers [24,25]. We were unable to adjust for the presence of HPV which has been found to be a predictor of survival in whites in America [26] as HPV testing was not routinely undertaken at the time of the study.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with non-Indigenous patients resident in Queensland, Australia, Indigenous people were diagnosed with more advanced cancer, had greater comorbidity, received less cancer treatment and were 30% more likely to die of their cancer; findings similar to those reported previously [5,6,15]. Concomitant disease is reported to influence cancer treatment choices (dose, duration, modality), cause complications, and impede survival [9,16-18].…”
Section: Discussionsupporting
confidence: 53%
“…A recent study in the Northern Territory (Australia)44 also found that of women diagnosed as having breast cancer, indigenous women were significantly more likely to be diagnosed as having advanced disease compared with non-indigenous women, suggesting this was due to later diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…Reasons for more advanced disease among indigenous women are varied and could include a reduced awareness of early symptoms of breast cancer, delay in seeking medical advice, poorer access and quality of screening and diagnostic services, and nihilistic beliefs about cancer and the chance of its cure causing reluctance to seek medical attention44 (personal communication, BreastScreen Queensland).…”
Section: Discussionmentioning
confidence: 99%